Cambios recientes en la diversidad de maíces criollos de Yucatán, México - Arias Reyes, Luis Manuel; Latournerie, L.; Montiel, S.; Sauri, E. (Universidad y Ciencia, Yucatán, MX, 2007)
The diversity and the genetic conservation of Maya traditional crops have been little studied. A comparative analysis of the germoplasm of the local varieties of maize from four samples collected in Yucatan (Mexico) over the last 50 years confirmed that the farmers prefer plants long-cycle yellow seeded variety x-nuuk nal. The planting of early maize varieties such as nal t’eel decreased possibly as a result of the introduction of improved maize. La diversidad y la conservación genética de los cultivos tradicionales mayas han sido poco estudiados. Un análisis comparativo del germoplasma de las variedades locales de maíz, provenientes de cuatro colectas realizadas en Yucatán durante los últimos 50 años, confirmaron la preferencia campesina en la siembra de maíces de ciclo largo x-nuuk nal amarillo. Asimismo, la siembra de variedades precoces como nal t’eel disminuyó posiblemente como consecuencia de la entrada de maíz mejorado.